THE SYSTEM OF STANDARDS IMPROVING FOR PLANNING REPAIRS OF ROLLING STOCK AND TRACK - Zenchuk, M. F. (Science and Transport Progress, 2008)
As far as wear of the rolling stock and the track related to movement of a train on a section occurs during overcoming the resistance to movement of a train, it looks expedient to conduct the account in a database of performed mechanical work of forces of resistance to movement on each locomotive, car and track section, and depending on amount of this work to make their repairs and replacement.